M1 and M2 Macrophage Polarization Correlates with Activity and Chronicity Indices in Lupus Nephritis - Chutima Chavanisakun; Rassamon Keawvichit; Nontawat Benjakul (Life)
Background: Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus (SLE), characterized by inflammation and immune dysregulation in the kidneys. The role of macrophage polarization in LN progression remains underexplored. Objective: This study examined the association between tubulointerstitial M1/M2 macrophage subpopulations and LN indices of activity and chronicity. Materials and Methods: We retrospectively reviewed 160 renal biopsy specimens in patients with LN (ISN/RPS classes II–V) from the database of the Department of Anatomical Pathology, the Faculty of Medicine Vajira Hospital, Navamindradhiraj University (2012–2021). Additional immunohistochemical analysis included CD68, iNOS, CD206, CD163, and evaluation of infiltration with M1 (iNOS+), M2a (CD206+), and M2c macrophages (CD163+). Moreover, clinical information at the time of the renal biopsy, including age, sex, and laboratory findings, was obtained from the electronic medical records. The data were correlated with the macrophage infiltration using the Spearman test. Results: Lupus nephritis biopsies with ISN/RPS class II–V were included (class II: 3 cases (2%), III: 30 cases (19%), III + V: 16 cases (10%), IV: 73 cases (46%), IV + V: 18 cases (11%), and V: 20 cases (12%)). In addition, the mean age of SLE patients at the time of biopsy was 33 years (range: 19–47 years). Most patients were females (n = 141; 88%). The population of CD68+ macrophages was related to serum creatinine (p < 0.001; rs = 0.34). We detected predominantly M2 macrophages across all LN classes, but M1 macrophages demonstrated significant correlations with the activity index (p < 0.001; rs = 0.43). Conversely, M2a and M2c subpopulations were strongly associated with the chronicity index (M2a: p < 0.001, rs = 0.48; M2c: p = 0.024, rs = 0.18). Total macrophages correlated with both indices (activity: p < 0.001, rs = 0.44; chronicity: p < 0.001, rs = 0.42). Conclusions: In lupus nephritis, the predominant population of macrophages is M2. Correlations were noted between the subpopulations of M1 and M2c macrophages and the activity and chronicity indices, respectively. In addition, macrophage populations correlated with disease progression, but the significance of this association in disease progression remains uncertain.